Diversity and activity patterns in the medium and large mammals in Alberto Manuel Brenes Biological Reserve, Alajuela, Costa Rica - Sánchez Porras, Ronald (2019)
Using the trap camera monitoring method, the medium and large mammal populations of the Reserva Biológica Alberto Manuel Brenes were recorded and analyzed on the La Fila trail. This reserve is located at the south of the Cordillera de Tilarán in Costa Rica, and this trail is located in the premontane humid tropical forest. The study was from February 2017 to February 2018. The use of trap cameras allowed obtaining video records, to analyze: relative abundance, diversity and activity patterns in medium and large mammals on the trail, during the dry and rainy season. Regarding relative abundance, a sampling effort of 1393 trap days was carried out, in which 410 individuals were recorded, with a total of 17 mammal species, in six orders and 11 families. The Carnivorous order was dominant with eight different species and Artiodactyla with 249 individuals. Pecari tajacu (IAR = 17.157, r = 239) and with a lower Mazama temama record (IAR = 0.071, r = 1). Among the threatened species were Tapirus bairdii (IAR = 0.9, r = 9) and Leopardus pardalis (IAR = 2.01, r = 28). In relation to diversity, the total specific richness of the sample was S = 17, the Margalef index indicates that diversity is high (dry season, Dmg = 3.18, rainy season, Dmg = 2.89), Pielou index showed, that in both seasons an abundance of diversity from medium to high (dry season, e = 0.63, rainy season e = 0.52) and Shannon-Wiener index shows a moderate diversity, with a total index of H'= 1.66, of a maximum of H'max = 2.7, (dry season H '= 1.79, rainy season H'= 1.46). The Hutchenson test shows that the Shannon Wiener index is significant in accepting that the rainy season does not have the same diversity as the dry season (n = 17, t = 2.41 p = 0.016, gl = 351). P. tajacu presented diurnal activity (7:00 - 19:00). Sciurus variegatoides, had its activity at night (20:00 - 06:00), L. pardalis presented nocturnal activity (20:00 - 06:00). The sampling carried out in this study allowed us to obtain significant information with 88.2% of the species of medium and large mammals present in the La Fila trail (ReBAMB), is based on the species accumulation curve.